Características del perfil del investigador en ciencias médicas y de la salud categoría Monge Medrano, calificado por el Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica de Perú, 2022. - Marin Samanez, Helen Stephani; Placencia Medina, Maritza Dorila (Revista Horizonte Médico)
Objective: To determine the profile of medical and health sciences researchers belonging to the Carlos Monge Medrano group, qualified by Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica (CONCYTEC - National Council of Science, Technology and Technological Innovation) and registered in Registro Nacional Científico, Tecnológico y de Innovación Tecnológica (RENACYT - National Scientific, Technological and Technological Innovation Registry) in 2022. Materials and methods: A quantitative, descriptive and cross-sectional study. The CTI Vitae - Hojas de vida afines a la Ciencia y Tecnología (CTI Vitae - Résumés related to Science and Technology) data sheets of 706 researchers registered in Renacyt were reviewed during September 2022. Demographic characteristics, academic background, career and scientific output were collected in a data collection sheet, which was used to create a database. Results: Out of all researchers, 65.3 % were males, 80.0 % came from Peru, and 66.7 % were fluent in two or three languages, the most frequent being Spanish, English, Portuguese, French, Italian, German and Quechua. As for their academic background, the highest degree was a doctorate (71.2 %), the first reported program was not always strictly a health sciences program, 80.3 % pursued master's studies and 71.2 % pursued doctoral studies. In addition, 75.5 % indicated a university as their primary affiliation. Regarding their career, 38.2 % had more than 20 years of work experience, 84 % served as educator, 51.7 % had experience as research project evaluator or developer and 74.8 % received an award or distinction during their career. Moreover, 133 researchers had an h-index between 4 and 6. Furthermore, 94.5 % (667 researchers) drafted scientific papers, out of whom 41.4 % were the lead author in one to five articles and 65.9 % served as undergraduate and graduate thesis advisor. Conclusions: Medical and health sciences researchers are mostly males, are fluent in at least two languages including English, have a doctorate degree and have scientific output. Universities are the most frequent institution of affiliation reported by researchers.